Co-production 'thinking' and performance implications in the case of separate waste collection. Issue 2 (1st February 2022) - Landi, Stefano; Russo, Salvatore
ABSTRACT: The relevance of co-production paradigm in recent years suggests innovative observation methods in the context of public-service delivery while marking the advent of a new way of 'thinking' in public service logic. From this perspective, co-production processes within separate waste collection are investigated. An index, drawn on co-production literature, is built to measure the public officers' co-production attitude. The association between the attitude in stimulating co-production and separate collection performance is tested controlling for 'classic' determinants already found in waste management literature. Results show that a higher attitude towards enhancing users' co-production facilitates the best achievements in terms of separate collection results.